2003
DOI: 10.1046/j.1365-2893.2003.00440.x
|View full text |Cite
|
Sign up to set email alerts
|

Lamivudine treatment during pregnancy to prevent perinatal transmission of hepatitis B virus infection

Abstract: Vertical transmission of hepatitis B virus (HBV) can occur occasionally despite vaccination of the child. This vaccination breakthrough has been associated with high maternal viraemia. We treated eight highly viraemic (HBV-DNA >/= 1.2 x 10(9) geq/mL) mothers with 150 mg of lamivudine daily during the last month of pregnancy. HBV-DNA, hepatitis B surface antigen (HBsAg), anti-HBs and anti-HBc of their offspring were measured at birth and at 3, 6 and 12 months, respectively. Twenty-four children, born to untreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
172
1
11

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(187 citation statements)
references
References 18 publications
3
172
1
11
Order By: Relevance
“…For women who become pregnant while receiving oral NA therapy, current guidelines recommend continuing treatment if the drug is a category B drug such as telbivudine and tenofovir [34]. Emerging evidence suggests that the use of lamivudine in the last month of pregnancy might prevent mother-to-infant transmission of HBV in women with high HBV DNA levels [36][37][38][39][40].…”
Section: Antiviral Treatment Options For Chb In Women Of Childbearingmentioning
confidence: 99%
See 2 more Smart Citations
“…For women who become pregnant while receiving oral NA therapy, current guidelines recommend continuing treatment if the drug is a category B drug such as telbivudine and tenofovir [34]. Emerging evidence suggests that the use of lamivudine in the last month of pregnancy might prevent mother-to-infant transmission of HBV in women with high HBV DNA levels [36][37][38][39][40].…”
Section: Antiviral Treatment Options For Chb In Women Of Childbearingmentioning
confidence: 99%
“…The proposal to use oral antiviral agents to reduce maternal HBV DNA serum levels in the third trimester and immediate postnatal period to avoid mother-tonewborn transmission was evaluated in a pilot study using antiviral therapy, such as lamivudine, in the third trimester to reduce maternal serum HBV DNA level by the time of birth [37]. However, the trial did not yield convincing efficacy results.…”
Section: Prevention Of Mother-to-child Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herd immunity induced by mass or nation-wide vaccination programs is well documented. [52][53][54] Preliminary studies have shown that lamivudine [55][56] and telbivudine 57 during pregnancy may reduce vertical transmission of HBV. Maternal to infant transmission may occur during the antenatal, intrapartum, or postnatal period.…”
Section: Discussionmentioning
confidence: 99%
“…Continuing efforts are needed to prevent breakthrough infection of HBV by highly infectious mothers. Preliminary results using anti-HBV nucleoside analog during the last trimester of pregnancy to prevent mother-to-infant transmission have been reported (van Zonneveld et al 2003;Xu et al 2009;Han et al 2011). However, further studies are needed to determine the efficacy versus adverse responses and cost effectiveness in reducing mother-to-infant transmission from highly viremic mothers.…”
Section: Vaccine Failurementioning
confidence: 99%